2007
DOI: 10.1016/j.vph.2007.06.007
|View full text |Cite
|
Sign up to set email alerts
|

The effects of estrogen and testosterone on gene expression in the rat mesenteric arteries

Abstract: A dramatic difference exists in the timing of development of cardiovascular disease in men vs. women. The primary candidates underlying the cause of this gender difference are the sex steroids, estrogen and testosterone. The vasculature is considered to be a site of action of these steroids. In spite of these concepts there is little data on the direct effects of estrogen and testosterone on gene expression in the vasculature. In this study, ovariectomized Sprague Dawley rats were treated for 4 days with vehic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 71 publications
2
18
0
Order By: Relevance
“…FIGLA is known to be a transcription factor that regulates other oocyte-specific genes (Bayne et al 2004; Huntriss et al 2002; Liang et al 1997). DBP is also a transcription factor whose expression has been shown to be induced by both estrogen and testosterone (Eyster et al 2007). DBP is known to regulate the expression levels of factor IX (Boccia et al 1996), which is an essential vitamin K-dependent serine protease that participates in the intrinsic pathway of coagulation.…”
Section: Discussionmentioning
confidence: 99%
“…FIGLA is known to be a transcription factor that regulates other oocyte-specific genes (Bayne et al 2004; Huntriss et al 2002; Liang et al 1997). DBP is also a transcription factor whose expression has been shown to be induced by both estrogen and testosterone (Eyster et al 2007). DBP is known to regulate the expression levels of factor IX (Boccia et al 1996), which is an essential vitamin K-dependent serine protease that participates in the intrinsic pathway of coagulation.…”
Section: Discussionmentioning
confidence: 99%
“…ERs have been localized in human aorta, coronary, carotid, uterine and internal mammary artery, as well as umbilical vein [38]. In experimental animals, ERs have been identified in ovine uterine artery, rat aorta, mesenteric and carotid arteries, and mouse aorta [39, 40]. ERs have also been identified in veins of different species, but their responsiveness to estrogen has not been fully examined.…”
Section: Introductionmentioning
confidence: 99%
“…However, information regarding the global effects of different formulations of estrogens on arterial gene expression remains sparse. Work from our laboratory (Eyster et al, 2007; Rodrigo et al, 2003a; Rodrigo et al, 2003b) and others (Gao et al, 2006; Nakamura et al, 2004; Watanabe et al, 2004) have identified moderate effects of estrogen on gene expression in arterial tissue and cells.…”
Section: Introductionmentioning
confidence: 92%